El Salvador : Selected Issues; Background Notes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper presents background notes on El Salvador's economic growth, national savings, and implications of the Central American Free-Trade Agreement with the United States (CAFTA). The paper describes possible factors behind sluggish growth in El Salvador in recent years, and suggests that the medium-term growth outlook hinges on further structural reforms, including steps to improve competitiveness and further strengthen the public finances. The paper also highlights the factors behind the sharp decline in domestic savings in recent years, suggesting a possible Dutch-disease phenomenon.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet